PEMBELAJARAN AI PADA SEKOLAH DASAR DI KOLAKA SULAWESI TENGGARA: POTENSI DAN TANTANGAN BERDASARKAN STUDI LITERATUR - Sallu, Sulfikar; Saputra, Erwin Eka; Parisu, Chairan Zibar L.; Hasbi, Hasbi (Jurnal Sultra Elementary School, 2025)
Artificial Intelligence (AI) is increasingly being applied in elementary education to improve the quality of learning. This study analyzes the potential and challenges of implementing AI in elementary schools in Kolaka, Southeast Sulawesi, based on a literature study. Using the IMRAD (Introduction, Methods, Results, and Discussion) approach, this study examines various scientific sources related to the benefits and obstacles to implementing AI in elementary education. The results of the study indicate that AI can increase student engagement, enable personalized learning, and assist teachers in providing more effective feedback. However, there are challenges such as teacher readiness, limited infrastructure, and lack of supporting policies. This study emphasizes the need for teacher training, infrastructure development, and policy support so that AI can be optimally implemented in elementary schools. This study provides insights for academics, education practitioners, and policy makers in developing effective AI implementation strategies. Further studies are needed to explore the long-term impacts and the best models for integrating AI in elementary education in Indonesia.